Transformations in Afro-Amerindian and European Dances in the Caribbean - Bien-Aimé, Kesler (Ethnologies, 2024)
The work of nascent Haitian ethnology (1920-1960), and even later works, highlights a certain «exceptionality» of the Haitian cultural fact that Benedicty-Kokken et al. (2016) qualify as «epistemic ambivalence.» This attempts to extract Haiti from its Caribbean historical and cultural roots. Haitian traditions and folklore, perceived as «singular,» would therefore be self-generated. To discuss this, this article uses three key works of the Indigenous movement of the period. While scholars consider these two notions to be synonymous, ethnographic observations carried out in Haiti on the issue in 2022 and 2023 by the Haitian Institute | Heritage and Tourism (INAPAT) do not allow us to definitively draw the boundaries between these two categories. The use of the notion of tradition or folklore by tradition bearers, cultural mediators, collectors, troupes, and various dance schools, varies. Taking into account three variables—location, performance context, and the speaker’s social profile—this article invites us to reflect on the connections between Haitian dances, and especially on their Caribbean roots.